Are some of the stigmas of addictions culturally sanctioned?. (March 2017) - Corrigan, Patrick; Schomerus, Georg; Smelson, David
Summary: We provide three examples of how addiction stigma is sanctioned: (a) discrimination against people with addictions is often legal; (b) public health communications frequently use stigma to promote prevention; (c) some programmes, such as '12 steps' promote self-stigma. The implications of sanctioned stigma for stigma-change programmes are then discussed.